Prevalence of signs and symptoms of temporomandibular disorders in urban and rural children of northern hilly state, Himachal Pradesh, India: A cross sectional survey - Deepak Chauhan; Jairam Kaundal; Suneet Karol; Tripti Chauhan (Wolters Kluwer Medknow Publications, 2013)
Background: Temporomandibular disorders (TMDs) have been recognized as a common orofacial painful condition. Many epidemiological studies of TMDs in children and adolescents have been performed. However, the results of such studies have varied, and a comprehensive view of the prevalence and severity of symptoms and signs is difficult to obtain. Objectives: To determine the prevalence of signs and symptoms of TMDs among school children of Himachal Pradesh and to establish a baseline for comparison with future studies. Study Design: Cross sectional. Materials and Methods: A sample of 1188 school children in the age group of 9 and 12 years (males n = 650 and females n = 538), from randomly selected schools of rural and urban areas of Himachal Pradesh were included as study subjects. The survey was done according to the WHO Oral Health Assessment Form (modified). Results: The results of TMDs, i.e., clicking, tenderness and reduced jaw mobility showed that overall prevalence was 2.5% and the rest 96.5% were not suffering from these disorders. In 9 years age group, the prevalence was 1.6% whereas it was more than double, 3.5% in 12 years age group. Signs and symptoms of TMDs were determined to assess their oral health status. Statistical Analysis: SPSS version 15. Conclusion: This study contrasts with what is found in the other societies regarding the high prevalence of TMDs disorders.